"Landholding-patriarchy hypothesis" and women's autonomy in rural India: An exploration of linkage. Issue 3 (4th March 2014) - Goli, Srinivas; Maikho Apollo Pou, Ladumai
Abstract : Purpose: – The paper aims to find out how far the size of household landholding directs patriarchal traits and thus influence women's autonomy. Design/methodology/approach: – The study used a two-part methodology. The first part provides theoretical background based on existing literature on women's autonomy and related information in formulating the "landholding-patriarchy hypotheses". The second part of this study evaluates the empirical evidences of the association between the size of household landholding and women's autonomy. Findings: – Results indicate considerable variation in women's autonomy with the size of their household landholding: women's autonomy decreases with increasing size of household landholding. Evidence suggests that landholding directs patriarchal traits, as manifested in a reasonable influence on women's autonomy in rural India. Originality/value: – The paper innovates a means to understand the contributing factors to lowering women's autonomy, thus explore the relevance of "landholding-patriarchy hypothesis".